2022
DOI: 10.21037/jgo-22-499
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and efficacy outcomes of early-onset severe neutropenia due to paclitaxel or nanoparticle albumin-bound paclitaxel combined with ramucirumab in advanced gastric cancer: a multicenter retrospective cohort study

Abstract: Background: Paclitaxel or nanoparticle albumin-bound paclitaxel combined with ramucirumab (PTX/ nab-PTX + RAM) is widely used as second-line chemotherapy for advanced gastric cancer (AGC), but severe neutropenia often develops with this regimen. Although previous studies have reported that severe neutropenia is a favorable prognostic factor in cancer chemotherapy, it is unclear in AGC patients receiving PTX/nab-PTX + RAM. In addition, the risk factors for early-onset of severe neutropenia (EOSN) still remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…As mentioned in the result, the BSANPs-PTX- and PTX-treated groups had lower neutrophil counts than healthy mice, while the platelet level for the BSANPs-PTX group was higher than in healthy mice and that of the PTX group was lower than the healthy group. Studies showed the neutrophils and platelet levels can be related to outcome and recovery following chemotherapy [ 52 , 54 ], and thus, it can be predicted that ESBP-BSANPs-PTX treatment may lead to better hematological recovery and outcome than BSANPs-PTX and PTX treatments. This prediction is supported by the prolonged survival time of the ESBP-BSANPs-PTX-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the result, the BSANPs-PTX- and PTX-treated groups had lower neutrophil counts than healthy mice, while the platelet level for the BSANPs-PTX group was higher than in healthy mice and that of the PTX group was lower than the healthy group. Studies showed the neutrophils and platelet levels can be related to outcome and recovery following chemotherapy [ 52 , 54 ], and thus, it can be predicted that ESBP-BSANPs-PTX treatment may lead to better hematological recovery and outcome than BSANPs-PTX and PTX treatments. This prediction is supported by the prolonged survival time of the ESBP-BSANPs-PTX-treated mice.…”
Section: Discussionmentioning
confidence: 99%